El e-Commerce como modelo competitivo para la educación continua virtual en Riobamba. - Arevalo Tapuy, Heidy Lizbeth (2023)
This research paper identifies the importance of considering e-commerce as a competitive model in Riobamba City. The study aimed to determine the incidence of e-commerce strategies in virtual continuing education. Currently, e-commerce and various businesses have seen the need to adapt to change and innovation, from which education should not be excluded. E-commerce is growing daily due to the increase in online sales compared to the decrease in sales of in-person businesses. Every day, more companies know the advantages of online marketing and proper e-commerce management. The digital revolution in education came to stay. E-commerce has enormous potential to improve the quality of education. One of the pillars of development in education is to broaden the perspectives for a future reality. E-commerce can enhance the quality of education in many ways. It opens the door to a wealth of information, knowledge, and educational resources, increasing learning opportunities inside and outside the classroom. The internet-supported interactive teaching method allows teachers to pay more attention to the individual needs of each student and supports shared learning. Every day, more people are interested in finding a new discipline or specializing in something they like or need for their work.